Formulation of Black Cumin (Nigella Sativa L.) Ethanol Extract Gel Preparation with Addition of Dimeticone as Hair Tonic - S, Wulansari; J, Reveny; M, Nainggolan (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to formulate a gel preparation for the ethanol extract of Black Cumin (Nigella sativa L.) with the addition of dimethicone as a hair tonic. Methods: Characterization examinations of Black Cumin (Nigella sativa L.) simplicia were carried out. Simplicia is macerated using 80% ethanol and concentrated in a rotary evaporator then in a freeze dryer until the extract is thick. The concentrations taken are 3%, 5% and 7%. Then tested the simplicia characterization, rat hair growth activity and an evaluation of the preparations was carried out, namely the homogeneity, organoleptic test, and microbial contamination test. Results: The results of the simplicia characterization test were water content of 6.63%, water soluble content of 24.64%, total ash content of 3.55% and acid insoluble ash content of 0.29%. Hair tonic preparations are stable in storage for up to 12 weeks from organoleptic, homogeneity. The hair growth activity of the ethanol extract hair tonic gel from 3 concentrations, the best was 7% (1.96 ± 0.00). Conclusion: Black Cumin (Nigella sativa L.) ethanol extract gel has hair growth activity.